Políticas públicas de formação docente para a educação escolar quilombola : concepções e práticas (2002-2019) - Santos, Leandro dos (2022)
This research has as its object of study the public policies of teacher training for quilombola school education that were institutionalized in Brazil from 2002 to 2019. Therefore, the objective is to investigate the conceptions put in such policies by the Brazilian educational system in the period considered, in order to verify how they are presented in the Political Pedagogical Project of the remaining quilombo municipal schools in the State of Sergipe. To achieve this objective, a bibliographic, documentary and empirical survey was carried out, which is historically reported in terms of the methodology adopted by the research and seeks to understand the real context of the quilombola communities in that State, which have passed through a complex system of social exclusion. Nowadays, quilombola communities continue to fight for recognition and identity strengthening, with education being a fundamental path constituted throughout their transformation process. The theoretical foundation of the research is based on the specific line of analysis built from a historical-dialectical contextualization of the object of study, in order to compose a set of conceptual elements that have as their starting point the social relations of production, emancipation, resistance, historicity, criticality, formation, culture, race and ethnicity. Thus, the analysis seeks to appropriate the essential parameters necessary to carry out an investigation of reality from its historical and social context. Consequently, with regard to its methodological basis, the research is based on the perspective of historical and dialectical materialism, as it is understood as a method of investigation capable of analyzing reality as a whole, as well as understanding the particular elements that are incorporated into the analyzed object. Through this analysis, it was possible to understand the contradictions of teacher training policies legitimized for the field of quilombola school education in Brazil throughout the period studied. The research concludes that these policies lack greater functionality in terms of their conceptions and the practices they give rise to, as they were produced within a set of actions that failed to institutionalize parameters capable of integrating the fundamental concepts for teacher training within the scope of quilombola school education. Among the actions that should be implicit in the policies considered, there is the need for teacher training that is capable of dialoguing with the differences and specificities of the remaining quilombo communities.